The Effect of Applying the Lean Manufacturing System on The Cost of Products in the Food Industry Sector by Applying it to the Sarayo Alwadiya Factories Group for Food Industries - Mohammed Al Raee (Advanced Research in Economics and Business Strategy Journal)
The study aimed to test the effect of applying the lean manufacturing system on the cost of products in the food industry sector by applying it to the Sarayo Alwadiya factories Group for Food Industries. The study used the descriptive analytical method, and it depended on the questionnaire tool to collect primary data, who are (75) employees, and the method of structural analysis has been applied Multilevel to devise the lean manufacturing system variale based on the idea of the interaction of the dimensions of the independent variable and measure its effect on the cost of products in the group. The study reached a set of results, the most important of which was the presence of a significant effect of the lean manufacturing system on the cost of products in the Sarayo Alwadiya Group for Food Industries where the value of this effect was (0.703), The most influential dimensions of the independent variable on the cost of industrial production were "worksite organization." with an impact value of 0.094, The study recommended that the group should focus on applying the production system on time and activating the reliance on the idea of cellular manufacturing